The potential microbial inactivation mechanisms of reduced graphene oxide functionalized textiles - Qinghong Huang; Tianyu Kou; Mingrui Liao; Tianhao Ge; Jing Liu; Jian R. Lu; Heng Zhai; Yi Li (Materials & Design)
Disinfection is crucial for medical protective clothing (MPC), as improper disinfection may cause secondary transmission during use and after disposal, especially for reusable MPC (RMPC). Reduced graphene oxide (rGO), a photosensitive material, has the potential to kill microorganisms by generating heat or voltage on textiles. To investigate this, we tested both photothermal and photovoltaic effects of rGO coated canionised (Cat-rGO) cotton fabric and the wet spinning rGO yarn with the xenon lamp, and a series of physical properties were also tested. Results show that under sufficient light intensities, Cat-rGO fabric easily reaches temperatures that can kill various common viruses, evidently inactivate both Escherichia coli and Staphylococcus aureus, and dries faster than pristine fabric. For rGO yarn, its temperature is significantly lower than Cat-rGO fabric when attached on common cotton fabric. As for photovoltaic effect, however, only rGO yarn can generate a voltage under light exposure, while Cat-rGO fabric does not. Despite this, in general, using the photothermal effect of Cat-rGO fabric to kill microorganism is more effective. This study demonstrates that Cat-rGO fabric can disinfect using light alone, without chemicals, metals, or extra equipment. It is an ideal choice for self-disinfecting RMPC and for use in medical facilities.